Malaria elimination: needs assessment and priorities for the future - El-Moamly, Amal (The Journal of Infection in Developing Countries, 2013)
When the World Health Organization announced the goal of global eradication of malaria in 2007, questions were raised about the naivety of this proposition. Since then, experts have been divided about this goal. Some scientists suggest that when defeating malaria, elimination is a worthy and challenging aim, but this has to be done with modesty and thorough analysis. Others believe that it is time to repeat the experience of smallpox eradication and to open a whole new era for public health, the eradication of many diseases. The opposing view suggests that raising expectations and failing again may set malaria control back, rather than advance its cause. This literature review focuses on malaria elimination. It summarizes the history of malaria elimination, its success factors and reasons for failure, and the controversial issues in malaria elimination. The collected articles on the challenges of elimination, and the technical and financial feasibility that countries must appreciate before proceeding, are identified. Also, this review discusses the current global strategy to eliminate malaria and highlights the main concerns for future plans aimed at elimination. These plans foresee improving currently available diagnostic methods, therapeutic and prophylactic agents and protocols, vector control procedures, vaccine development progress, and other operational tools and approaches. Finally, this review addresses a number of research priorities in the present stage of the fight against malaria.